The Political Ecology of Chinese Investment in Uganda: the Case of Hanhe Farm - Josh Maiyo (China Africa Research Initiative (CARI), School of Advanced International Studies (SAIS), Johns Hopkins University, 2014)
How is Chinese agricultural investment progressing in Africa? Research reported at the SAIS-CARI conference in May 2014 suggests the topic is poorly understood and that investment is both far lower and far more problematic in implementation. In our first CARI policy brief, Josh Maiyo looks into Chinese private farming in Uganda. Media reports depict at least 12,000 hectares of private Chinese agricultural investment. Doing fieldwork in Uganda, Maiyo found only one farm, Hubei Hanhe, with 160 hectares. His story of the Hubei Hanhe Farm is a cautionary tale of a much more contentious, challenging investment environment than is often assumed.
Keywords: 330